Exploring the motives for using social networks for professional development by Spanish teachers - Marcelo-Martínez, Paula; Yot-Domínguez, Carmen; Mosquera Gende, Ingrid (Information and Learning Sciences, 2024)
Purpose – Social networks (SNs) play a significant role as environments supporting teacher professional development. The purpose of this to analyze the motivation and participation roles that Spanish teachers have when participating in SNs for their professional development in three professional stages: preservice teachers, beginning teachers and experienced teachers. Design/methodology/approach – The study uses a mixed-method approach, combining two validated surveys, one applied to 217 preservice teachers and other to 68 beginning teachers and 384 experienced teachers, with 15 interviews. A qualitative exploratory sequential strategy has been followed along with an ex post facto quantitative survey-type study of a descriptive and inferential nature. Findings – Preservice and beginning teachers use SNs to access materials and resources with which to learn, presenting an observer and passive role in their interaction on SNs. Experienced teachers log in to learn about experiences but begin to participate more actively in SNs for searching for specific resources, establishing contacts with other teachers, contributing with their own educational materials and helping other teachers with their doubts or even forming their own communities. Originality/value – These findings help understand how the evolution in teacher expertise accompanies the level of involvement in their social network interactions. The results allow us to better understand how different levels of teaching experience influence the way Spanish teachers access and participate in SNs, in some cases consuming and in others producing digital content.
Keywords: social networks; teacher professional development; lifelong learning; informal learning; preservice teachers; beginning teachers; experienced teachers